Short‐chain fatty acids mediate gut microbiota–brain communication and protect the blood–brain barrier integrity - Chenghan, Mei; Wanxin, Li; Bangcheng, Zhao; Yao, He; Qinxi, Li; Ting, Zhang; Xiaojie, Li; Kun, Zhang; Yingqian, Zhang; Zhihui, Zhong (Annals of the New York Academy of Sciences, 2025)
The human gut, with a complex community of microbes, is essential for maintaining overall health. This gut microbiota engages in two‐way communication with the central nervous system, collectively known as the gut microbiota−brain axis. Alterations in gut microbiota have been associated with various neurological disorders, and disruptions to the blood–brain barrier (BBB) may be crucial, though the exact mechanisms remain unknown. In the current study, we investigated the impacts of short‐chain fatty acids (SCFAs) on the integrity of the BBB, which was compromised by orally administered antibiotics in rhesus monkeys and C57BL/6n mice. Our results showed that SCFA supplementation notably enhanced BBB integrity in rhesus monkeys with gut dysbiosis. Similar outcomes were observed in mice with gut dysbiosis, accompanied by decreased cortical claudin‐5 mRNA levels. In particular, propionate, but not acetate or butyrate, could reverse the antibiotic‐induced BBB permeability increase in mice. Additionally, in vitro studies demonstrated that propionate boosted the expression of tight junction proteins in brain endothelial cells. These results suggest that the propionate can maintain BBB integrity through a free fatty acid receptor 2–dependent mechanism. This study offers new insights into the gut−brain axis and underscores potential therapeutic targets for interventions based on gut microbiota. Alterations in gut microbiota are associated with neurological disorders and blood‐brain barrier (BBB) disruption. Short‐chain fatty acid supplementation improved BBB integrity in rhesus monkeys and mice with oral antibiotic–induced gut dysbiosis. Propionate, but not acetate nor butyrate, reversed the increase in oral antibiotic‐induced BBB permeability. Additionally, propionate administration boosted the expression of tight junction proteins in brain endothelial cells. Propionate can maintain BBB integrity in an FFAR2‐dependent way.